Advanced organic chemistry : reaction mechanisms - Brückner, Reinhard, 1955- (Harcourt/Academic Press, 2002)
A best-selling mechanistic organic chemistry text in Germany, this text's translation into English fills a long-existing need for a modern, thorough and accessible treatment of reaction mechanisms for students of organic chemistry at the advanced undergraduate and graduate level. Knowledge of reaction mechanisms is essential to all applied areas of organic chemistry; this text fulfills that need by presenting the right material at the right level.
Keywords: Organic reaction mechanisms.; Chemistry, Organic.; elektronické knihy; electronic books